Pediatric non-urgent emergency department visits and prior care-seeking at primary care - Nithin Ravi; Katherine M. Gitz; Danielle R. Burton; Kristin N. Ray (BMC, 2021)
Abstract Background We aimed to examine how caregiver perceptions of primary care affects care-seeking prior to pediatric non-urgent ED visits. Methods We performed a cross-sectional survey of caregivers of children presenting to a pediatric ED during weekday business hours and triaged as low acuity. We first compared caregiver sociodemographic characteristics, perceptions of primary care, and stated preference in care sites (ED vs PCP) for caregivers who had sought care from their child's PCP office versus had not sought care from their child's PCP office prior to their ED visit. We then examined odds of having sought care from their PCP office prior to their ED visit using multivariable logistic regression models sequentially including caregiver primary care perceptions and stated care site preferences along with caregiver sociodemographic characteristics. Results Of 140 respondents, 64 (46%) sought care from their child's PCP office prior to presenting to the ED. In unadjusted analysis, children insured by Medicaid or CHIP, caregivers identifying as Black, and caregivers with lower educational attainment were less likely to have sought PCP care before presenting to the ED (p < 0.005, each). Caregivers who had sought PCP care were more likely to prefer their PCP relative to the ED in terms of ease of travel, cost, and wait times (p < 0.001, all). When including these stated preferences in a multivariable model, child insurance, caregiver race, and caregiver education were no longer significantly associated with odds of having sought PCP care prior to their ED visit. Conclusions Differential access to primary care may underlie observed demographic differences in non-urgent pediatric ED utilization.